Pemanfaatan Barang Bekas Dalam Meningkatkan Kreativitas Anak-Anak Dusun 3 Desa Aman Damai - Lisa Dwi Afri; Mega Utami Hasibuan; Nisaiy Darussakinah Harahap; Ananda Aditya Sari Harahap; Siti Fatimah Sitorus; Dianny Rachma Khairia Batubara (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Creativity is a human potential that does not come from outside the individual. Data collection techniques carried out in the form of documentation and extracting information about innovative methods and utilization of used goods. The results of this service activity are based on observations that have been made in Aman Damai Village Hamlet 3 Sirapit District, namely some of the results show positive because the manufacturing process does not take much time, in making bookshelves from cardboard children show enthusiasm for the directions delivered by the service team, positive reactions shown by children to interest in making bookshelves where almost all participants are able to make and decorate bookshelves well, children follow the mechanism of making products and are quite good at working with the team and children's creativity develops quite well. With used goods can increase income and can help the family economy.